Проблеми фінансових можливостей, інтересів і відносин учасників у процесі оновлення житлового фонду - Блащук, О. В.; Саркісова, К. М. (Ways to Improve Construction Efficiency, 2013)
Defects in the system of financing updating of objects in the dwelling real estate are analysed, sources of funding,depending on the degree of wear and ownership of residential real estate objects are proposed.